The Role of Murobbi in Formation of Santri Morals at the Tahfizh Qur'an Islamic Boarding School Al Azka Putri Cisauk Tangerang - Ike Nita Nur Sundari; Lamya Hayatina; Amri Sanusi (State Islamic Institute of Palopo, 2022)
The main purpose of coaching in Islam is to form good morals or character. In the current era of globalization, you can find information quickly; if you cannot choose the right one, it can reduce morals among students. Therefore, the existence of moral development for students is very important. The moral formation, namely the polite attitude of students from their words and actions, aims to improve morality, especially polite attitudes towards Ustaz, ustazah, seniors, juniors, and other friends. The method or technique carried out in the research process is an effort in science that is used to obtain facts and principles patiently, carefully, and qualitatively. The problems studied in this study are: how is the role of murobbi in the formation of the morals of students in the female Tahfizh Qur'an Al Azka Islamic boarding school, and also the supporting and inhibiting factors for the formation of the students' morals in the female Tahfizh Qur'an Al Azka Islamic boarding school.